The Union's Efforts to Enhance Labor Relations in Nepal's Manufacturing Sector - Pant, Ganesh Datt (Journal of Development Review, 2023)
The purpose of a trade union is to represent the collective voice of workers for the improvement of the workplace and amenities for employees. Workers in various sectors organized trade unions to engage in collective bargaining with management for better amenities and perks after Nepal achieved democracy in 1950. The objective of the study is to find the effort of labor union to improve labor relation in Nepalese manufacturing organizations. The study based on descriptive analysis and concentrates on understanding the role of union in increasing earning, securing employment, providing time off, and paying overtime which are essential for improving labor relation at work. In order to perform the study, some workers were contacted, and the currently available literature was reviewed. The study concentrated on trade union efforts to enhance labor relations, pay, benefits, overtime pay, job security, health, and welfare in various time periods. Older employees were given an open-ended questionnaire to share their perspectives. The study concludes that labor management relation is influenced by trade union’s activities. Labor unions have evolved into full-fledged political organizations that harm workers' livelihoods.